Horizontal-Vertical-Rocking Coupled Response Analysis of Vertical Seismic Isolated Structure under Near-Fault Earthquakes. (23rd July 2020) - Liu, Dewen; Zhang, Yafei; Fang, Sitong; Liu, Yang
Abstract : For vertical isolated structures with excessive vertical eccentricity for mass and vertical stiffness, horizontal-vertical-rocking response needs to be better understood for vertical isolated structures located in near-fault areas, where long-period velocity pulse can be produced. In this study, a seismic isolation system including quasizero stiffness (QZS) and vertical damper (VD) is used to control near-fault (NF) vertical earthquakes. The responses of horizontal-vertical-rocking coupling base-isolated structure including quasizero stiffness (QZS) and vertical damper (VD) subjected to NF horizontal and vertical ground motions are investigated. Nonlinear dynamic analyses are conducted to study the effects of essential parameters such as isolation system eccentricity, static equilibrium position, vertical isolation period, and vertical damping ratio on seismic responses of vertical isolated structure. It is found that increasing vertical period and damping ratio causes the vertical isolated structures to behave well in reducing rocking responses of structure. The effect of horizontal-vertical-rocking coupling on vertical seismic isolation efficiency is insignificant. The vertical seismic isolation remains effective as compared to the system supported on rubber bearings. The vertical damping can significantly control the vertical displacement and rocking moment.